Observing Harry. - Arnold, Cath (McGraw-Hill International (UK) Ltd., 2007)
This book is about Harry, a determined little boy, who is intrinsically motivated to explore his world from an early age. His parents and grandparents find him so fascinating that they keep a written and video diary of Harry's play from when he is 8 months to five years. The author offers theories about how children learn and applies the theories to the observations of Harry. The book demonstrates how effectively Harry accesses each area of the curriculum through his interests. It shows how Harry develops coping strategies when the family experiences major changes. It also highlights the contr.